Pola Interaksi Spasial Sebaran UMKM dan Kontribusinya terhadap Pertumbuhan Ekonomi Wilayah di Kota Bima - Hanifah Muthiah; Amirulmukminin Amirulmukminin (Journal of Innovative and Creativity (Joecy), 2026)
This study aims to analyze the spatial interaction patterns of Micro, Small, and Medium Enterprises (MSMEs) distribution and measure their contribution to regional economic growth in Bima City using a Geographic Information System (GIS) approach. Primary data were collected through field surveys of 347 MSME units across 5 sub-districts, supplemented by secondary data from the Bima City Cooperative and SME Agency for 2022–2023. Analytical methods include Nearest Neighbor Analysis (NNA), Kernel Density Estimation (KDE), Moran's Index for spatial autocorrelation, and spatial regression analysis (Spatial Lag Model). Results show a clustered distribution pattern with a Nearest Neighbor Ratio (NNR) of 0.412. Three main MSME clusters were identified: Raba Sub-district (highest density at 48.7 units/km²), Rasanae Timur (37.2 units/km²), and Mpunda (29.6 units/km²). Moran's I index of 0.634 indicates strong positive spatial autocorrelation. Spatial regression analysis reveals that MSME concentration significantly affects per capita Gross Regional Domestic Product (GRDP) with a spatial spillover effect to neighboring sub-districts of 23.4%. The trade sector dominates (41.8%), followed by culinary and services (28.3%) and handicrafts (15.6%). These findings confirm that spatial agglomeration of MSMEs substantially contributes to Bima City's economic growth and provides a basis for integrated economic zone development policy recommendations.